Unique Needs and Challenges Experienced by Young People With Stroke: An International Qualitative Analysis - Demers, Marika; Charalambous, Marina; Kwah, Li Khim; Thilarajah, Shamala; Bazadona, Danira; Chapman, Sherita; Nasreldein, Ahmed; Yperzeele, Laetitia; Amoah, Dinah; Winstein, Carolee; Bernhardt, Julie; Gopaul, Urvashy (My University, 2025)
Stroke in young adults has a lifelong impact on activities of daily life, including driving, leisure, and community-based activities; social participation; and reduced productivity. The needs of young people with stroke (YPwS) are likely to vary across different countries, and the development of age-adapted information and interventions is therefore critical in addressing those needs. This study aims to (1) identify the unmet needs of people with stroke aged 18 to 55 years across countries with varied income levels and cultural backgrounds and (2) determine their preferred means to access knowledge and information about stroke in the young.